Effect of Toothing Schemes and Tooth Sizes on the Performance of Confined Brick Masonry Walls: A Parametric Study - Shandilya A.N.; Kumar V.; Haldar A.; Mandal S. (My University, 2025)
Confined brick masonry (CBM) employs in-situ cast reinforced concrete (RC) elements around small-height wall segments. The poured concrete fills gaps, covers protruding bars, and tightly secures the masonry walls through toothing at corners and openings. This secure connection is achieved through “toothing” in the masonry walls, strategically located at the corners and junctions. This study used numerical simulations in ABAQUS to determine the behaviour of CBM wall panels with different toothing schemes and tooth details during a seismic event. A non-linear finite element macro-model is used for the parametric study on CBM walls. The study found that machine-made hollow units with toothing improved lateral capacity by 12.0% more than the hand-made scheme and 12.20% higher than the toothing scheme with horizontal reinforcement. Furthermore, investigating different tooth sizes for the CBM wall showed that varying protruding brick’s vertical and horizontal spacing can significantly improve seismic performance. Specifically, the study found that closer vertical spacing, i.e., 100 mm of protruding bricks, provides 17.8% higher lateral capacity than the wall with a vertical projection of 200 mm, resulting in better seismic performance of CBM walls. These findings likely have significant implications for designing and constructing CBM walls in earthquake-prone regions since optimising toothing details can enhance seismic performance and increase overall safety. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.